Southern women in the recent educational movement in the South - Mayo, Amory Dwight (United States, 1892)
The South was the last region of the country to accept education for women. This book presents a detailed account of the various levels of education accessible to both white and black women in the South and describes southern women's participation in the movement for women's education.